ANALYSIS OF KAHLIL GIBRAN'S POEM الأم USING ROMAN JAKOBSON'S FORMALISM THEORY - Yusril Muhammad Nur; Agung Setiyawan (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
This study aims to analyze Khalil Gibran’s poem Al-Umm (الأم) using Roman Jakobson’s formalist theory, with particular emphasis on the poetic function and the linguistic representation of maternal love and a child’s affection toward the mother. The research adopts a qualitative interpretive approach that relies on close textual analysis to explore meaning as constructed through internal linguistic and stylistic features rather than external historical or biographical contexts. The primary data source is the poem Al-Umm, while data collection was conducted through careful reading and systematic note-taking. In this analysis, data reduction refers to the process of selecting, classifying, and focusing on relevant linguistic elements—such as figurative language, repetition, and imagery—that are directly related to Jakobson’s formalist framework. Data were then analyzed through interpretative procedures followed by conclusion drawing. The findings reveal that the poem highlights the role and character of a mother in shaping her children, as well as the emotional responses of children toward their mother, conveyed through expressive and symbolic language. To enhance its aesthetic structure and thematic depth, the poem employs six major language styles: poetic exaggeration (hyperbole), simile, repetition, anecdotal expression, representation or imagery, and associative language.